Systems of Differential Operators and Generalized Verma Modules - Kubo, T. (Symmetry, Integrability and Geometry: Methods and Applications, 2014)
In this paper we close the cases that were left open in our earlier works on the study of conformally invariant systems of second-order differential operators for degenerate principal series. More precisely, for these cases, we find the special values of the systems of differential operators, and determine the standardness of the homomorphisms between the generalized Verma modules, that come from the conformally invariant systems.